Regional Consumption Responses and the Aggregate Fiscal Multiplier - Bill Dupor; Marios Karabarbounis; Marianna Kudlyak; M. Saif Mehkari (Institute of Labor Economics (IZA), 2022)
We use regional variation in the American Recovery and Reinvestment Act (2009-2012) to analyze the effect of government spending on consumer spending. Our consumption data come from household-level retail purchases in the Nielsen scanner data and auto purchases from Equifax credit balances. We estimate that a 1 increase in county-level government spending increases local non-durable consumer spending by 0.29 and local auto spending by 0.09. We translate the regional consumption responses to an aggregate fiscal multiplier using a multi-region, New Keynesian model with heterogeneous agents, incomplete markets, and trade linkages. Our model is consistent with the estimated positive local multiplier, a result that distinguishes our incomplete markets model from models with complete markets. At the zero lower bound, the aggregate consumption multiplier is twice as large as the local multiplier because trade linkages propagate the effect of government spending across regions.
Keywords: E21; E62; H31; H71; 330; consumer spending; fiscal multiplier; regional variation; heterogeneous agents